Minat Siswa SMK Pariwisata Jurusan Tata Kecantikan Memilih Prodi Pendidikan Tata Rias dan Kecantikan Universitas Negeri Padang - Selfia, Mega; Rostamailis, Rostamailis; Astuti, Murni Astuti (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
The background of this researchÂ was concern from the low interest of SMK tourism students who monoring system beauty choosing Education Makeup and Beauty Family Welfare FT UNP, it can be seen from lower input from SMK students that is relevant with Education Makeup and Beauty. This research was aimed to reveal the interest of SMK Tourism who majoring Education Makeup and Beauty KK FT UNP. This research was quantitative descriptive. Population and sample of this research where all of the SMK tourism students in particular 6 and 7 Padang at class XII System Beauty department totaling 68 students. The technique of data collection was questionnaire, the data analisis using the percentage of data respondents for the level of a chievement of the overall everage scaves and data classification techniques using mean Ideal (MI) and Standard Deviation Ideal (SDI). Based on the result of SMK Tourism Padang student, gained affention indicator percentage of 67 % ned moderate category, motivate power indicator obtained score of 55 % had low category, and indicator of good feelings obtained score of 60 % nad low category. The resuts of this research was suggested to Family Welfare Department particularly Education Makeup and Beauty department to give wider information about Education Makeup and Beauty department Â Â Kata Kunci : Minat Siswa, Memilih Prodi Pendidika Tata Rias dan Kecantikan